2015
DOI: 10.1039/c5ta01399b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the behavior of Li–oxygen cells containing LiI

Abstract: This work deals with core issues of Li–oxygen battery systems; intrinsic stability of polyether electrolyte solutions and the role of important redox mediators such as LiI/I2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
237
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(263 citation statements)
references
References 44 publications
23
237
2
1
Order By: Relevance
“…Although the formation of side products occurs in all solvents, it is less severe in ether-based cells than in carbonate-based ones 129,144 . In a recent series of papers [146][147][148][149] , it was demonstrated that all relevant non-aqueous solvents are reactive towards basic and nucleophilic O 2 reduction products (that is, superoxide and peroxide moieties) in the solution phase containing highly electrophilic Li ions. We note that all carbonaceous electrode materials can degrade by reacting with superoxide and peroxide moieties.…”
Section: Metal-oxygen Battery Systems Secondary Li-o 2 Batteries Wermentioning
confidence: 99%
“…Although the formation of side products occurs in all solvents, it is less severe in ether-based cells than in carbonate-based ones 129,144 . In a recent series of papers [146][147][148][149] , it was demonstrated that all relevant non-aqueous solvents are reactive towards basic and nucleophilic O 2 reduction products (that is, superoxide and peroxide moieties) in the solution phase containing highly electrophilic Li ions. We note that all carbonaceous electrode materials can degrade by reacting with superoxide and peroxide moieties.…”
Section: Metal-oxygen Battery Systems Secondary Li-o 2 Batteries Wermentioning
confidence: 99%
“…2. In this case, the minimum potential required to oxidize Li 2 O 2 (s) is 2.96 V, and the iodide/triiodide redox couple possesses the required driving force to carry out this reaction, as shown in several experiments (6).…”
mentioning
confidence: 88%
“…Previous reports have shown empirical evidence of parasitic reactions associated with iodide/triiodide redox couples in a Li-O 2 battery with ethereal solvents (6,7). Such irreversible routes obviously need to be avoided to allow long-term rechargeability in a Li-O 2 battery.…”
mentioning
confidence: 99%
“…One of the requirements for the mediator is its stability to the electrochemical conditions, in effect we found UV-visible spectroscopy evidence that oxygen actually reacts with the mediator iodide [31]. Other authors instead have shown that the product may also be significantly affected by iodide [32]. By comparing Figure 12 with Figure 11 we could not notice any remarkable difference in the morphology or composition of fully discharged electrodes with or without iodide.…”
Section: Redox Mediators and Rechargementioning
confidence: 55%